Bayesian Network Meta-Analysis of Postoperative Analgesic Techniques in Thoracoscopic Lung Resection Patients - Fang Yue; Yongye Xie; Xiangdong Chen; Ruifen Xu; Hui Wang; Ning Bai; Minna Hou; Jiao Guo (Pain and Therapy)
Abstract Introduction Postoperative analgesia in thoracoscopic lung resection is crucial, with several nerve block techniques—including thoracic epidural anesthesia (TEA), paravertebral block (PVB), erector spinae plane block (ESPB), intercostal nerve block (INB), and serratus anterior plane block (SAPB)—commonly employed. However, there remains ongoing debate regarding the optimal technique. Methods To evaluate and compare the effectiveness of these analgesia methods, a systematic review was conducted across multiple databases, including PubMed, Embase, Web of Science, and the Cochrane Library, identifying relevant randomized clinical trials (RCTs). A Bayesian network meta-analysis was performed to assess postoperative pain management, with subgroup analyses and meta-regression conducted to examine key factors influencing outcomes, such as the risk of bias, continuous catheter analgesia, and patient-controlled analgesia (PCA). Results The results revealed that for 12-h resting visual analog scale (VAS) scores, the surface under the cumulative ranking curve (SUCRA) ranking was TEA > PVB > ESPB > control > INB > SAPB, whereas at 24 h, it shifted to PVB > TEA > ESPB > INB > control > SAPB. For 12-h coughing VAS scores, TEA ranked highest, followed by PVB, SAPB, ESPB, and control. At 24 h, PVB ranked highest, followed by TEA, ESPB, SAPB, INB, and control. The inconsistency test showed good consistency, with minimal publication bias, and meta-regression revealed that neither study quality nor local anesthetic infiltration at the incision site significantly impacted the outcomes. Excluding studies without PCA did not change the SUCRA rankings. PVB consistently ranked highest for 24-h resting and coughing VAS scores. Clustered ranking plots indicated that PVB and ESPB were the most suitable techniques for postoperative analgesia. Conclusion PVB and ESPB emerged as the most suitable analgesic techniques for thoracoscopic lung resection. While PVB showed superior analgesic efficacy, ESPB offered fewer side effects, providing a safety advantage. TEA was considered less suitable due to its excessive side effects.